Sustainable one-pot platform for the green recovery of carotenoids from Phaffia rhodozyma yeast and their use as natural additives in soap formulation - Mussagy, Cassamo U.; Farias, Fabiane O.; Santos-Ebinuma, Valeria C. [UNESP]; Pereira, Jorge F.B.; Pessoa, Adalberto (Elsevier, 2023)
Microbial-based pigments have attracted the interest of the cleaning and cosmeceutical industries as greener and more effective alternatives to the synthetic antioxidants and antimicrobials used in commercially colored soaps. Astaxanthin and β-carotene are natural carotenoids with strong antioxidant activity produced by yeast Phaffia rhodozyma (P. rhodozyma), but its use in industrial-scale processes is still very scarce. The optimization of downstream processing operations for the recovery of carotenoids from P. rhodozyma using environmentally and energetically favorable processes has not yet been fully achieved. In the present work, we propose a simple and sustainable one-pot process using biocompatible and renewable solvents (ethanolic carboxylic acids mixtures) for the recovery of astaxanthin and β-carotene from P. rhodozyma biomass and direct formulation of bioactive soaps, thus minimizing the processing units. For this purpose, carotenoids-enriched ethanolic carboxylic acids solutions were directly (“one-pot”) used in the following saponification process for the formulation of bioactive soaps without the need for additional purification units. The recovery aptitude of ethanolic carboxylic acids solutions and the corresponding solvation mechanisms of different solvent mixtures for astaxanthin and β-carotene were screened using the COSMO-SAC model. Operating parameters (e.g., solvent ratio, time extraction, temperature, and re-extraction cycles) were optimized for the solvent mixture (ethanol:lauric acid) that exhibited the highest recovery capacity for both carotenoids. The incorporation of microbial carotenoids in formulated soaps decreases the moisture content (from 10.04 to 6.85%), the pH (from 8.83 to 8.68), and the surface hardness (from 0.68 to 0.60 mm) and increase the foam height (from 5.83 to 7.07 cm). The biological activity of carotenoids-rich soaps was confirmed by antioxidant tests (60.53%). This work demonstrated that mixing natural yeast-based carotenoids with biosolvents is a simple, effective and sustainable solution for the formulation of functional and colored soaps.
Keywords: Astaxanthin; Carboxylic acids; Natural antioxidants; Phaffia rhodozyma; Soap formulation; β-carotene